2001
DOI: 10.1128/aem.67.3.1232-1238.2001
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Six Peptidases from Lactobacillus helveticus in Lactococcus lactis

Abstract: For development of novel starter strains with improved proteolytic properties, the ability of Lactococcus lactis to produce Lactobacillus helveticus aminopeptidase N (PepN), aminopeptidase C (PepC), X-prolyl dipeptidyl aminopeptidase (PepX), proline iminopeptidase (PepI), prolinase (PepR), and dipeptidase (PepD) was studied by introducing the genes encoding these enzymes into L. lactis MG1363 and its derivatives. According to Northern analyses and enzyme activity measurements, the L. helveticus aminopeptidase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 34 publications
0
31
2
Order By: Relevance
“…The postproline hydrolysis of PepF, PepO2, and PepO3 toward ␤-CN (f193-209) and ␣ S1 -CN (f1-9) under cheese-ripening conditions suggests that these enzymes may contribute to the debittering activity of L. helveticus CNRZ32. Genes from lactobacilli have been previously expressed in L. lactis (10,39) using the inducible nisA promoter, the L. helveticus pepX promoter, or their own promoters (22,25). A previous study of L. helveticus CNRZ32 promoter strength, which used ␤-glucuronidase as the reporter gene, found that pepO and pepO2 promoters were weakly expressed in L. lactis (7).…”
Section: Discussionmentioning
confidence: 99%
“…The postproline hydrolysis of PepF, PepO2, and PepO3 toward ␤-CN (f193-209) and ␣ S1 -CN (f1-9) under cheese-ripening conditions suggests that these enzymes may contribute to the debittering activity of L. helveticus CNRZ32. Genes from lactobacilli have been previously expressed in L. lactis (10,39) using the inducible nisA promoter, the L. helveticus pepX promoter, or their own promoters (22,25). A previous study of L. helveticus CNRZ32 promoter strength, which used ␤-glucuronidase as the reporter gene, found that pepO and pepO2 promoters were weakly expressed in L. lactis (7).…”
Section: Discussionmentioning
confidence: 99%
“…This revealed that both proteolytic and biosynthetic enzymes could be expressed through the same mRNA (35). Recently, six L. helveticus peptidase-encoding genes, including pepR, were expressed in Lactococcus lactis under the control of their own promoters (16). pepD and pepR were the only two peptidases for which no expression in Lactococcus lactis was obtained.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of an outer membrane in these gram-positive microorganisms makes them particularly attractive for the display or secretion of biologically active molecules such as antigens, enzymes, or cytokines (4,19,30,31). In addition to being considered nonpathogenic, LAB show a remarkable ability to survive passage along the oral route, as documented by their active metabolism in most of the compartments of the gastrointestinal tract (3).…”
Section: Discussionmentioning
confidence: 99%